Remittances, Trade Openess and Financial Sector Development in Nigeria - Yusuf Shamsuddeen Nadabo (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
The purpose of this study explores the impact of remittances on financial sector development in Nigeria data spanning from 1990 to 2021. The study used Autoregressive Distributed Lag (ARDL) and Toda Yamamoto (TY Causality) technique to examine the relationship between remittances and financial sector development. The result of the study indicates that remittances were found to have a positive significant impact on financial sector development during the period of the study real interest rate is also found to have a negative impact on financial sector development in Nigeria. Lastly, trade openness is found to have a positive statistically significant impact on financial sector development in Nigeria. The study recommends having established that remittances inhibit financial sector development, the government should employ policies that will encourage channeling remittances through a formal banking system. As well as ensuring that such remittances received are channeled to finance productive investment hence financial development. The novelty of this research lies in the fact that the study is against the few empirical studies that focused only on uncomplicated techniques in their analysis of data. Also, the study made use of the two main indicators of remittances in an economy, which are, trade openness, and real interest rate, to examine its impact on financial development in Nigeria.